The Turkish, Islamic-like Phenomenon of Mystic Orders. Possibilities for a Cultural Syncretism in the Geopolitical Perspective of International Mutual Understanding. - Ioannis Mazis (Geopolitics: theory and praxis, 2002)
Our effort in this text aims to identify the possibilities for mutual cultural understanding between civilizations of the Eastern- and Western- type (e.g. Turkey and Greece), on the one hand, and to suggest, on the other, that more challenges exist -from a geopolitical point of view- which could be exploited by future Turkish actors of power, whose intentions are not always clear. As will be clarified throughout this text, it is our belief that everything depends on the intentions of those who control these political tools. Indeed, only their democratic management may lead to the result which the peoples of the Eastern Mediterranean long for, i.e. peace, international justice and respect for the human rights and political freedoms of their nations and national groups. Nevertheless, any special reference to the Turkish Islamic internalized -as well as comparative- Sufi fraternities should be superseded by an overview of the Islamic and the Sufi syncretic Fraternities, their place in history, as well as by their examination in terms of ideology, in the framework of modern Islam and of the modern Turkish society. It is through this course of examination that we shall be able to draw conclusions on the correlation of these Fraternities with political activity, and to determine the forms, the levels and the qualities of this activity -which is placed well beyond the strict orthodox limits of the official Sunnite Islam of the state and viewed with mixed emotions by the governmental Directorate of Religious Affairs, the Diyanettleri Başkanhi. First of all, we should acknowledge the social necessity of this concept, i.e. the internalized and ideologically, eschatologically, and ethically “charged” Islam, as contrasted to the “dehydrated” legalistic Islam -whose only concern are the Five Fundamental Religious Duties and the observance of the Shari’a. This “internalized Islam”, an Islam so complex and unknown and not susceptible of generalizations, an Islam which in the final analysis is an “Islam of veneer”, consists essentially of a part of the widespread network of the Orders that have been present and operating in the Muslim world for around eight centuries. These Orders must be examined from this -geopolitical- perspective and clearly classified as Islamic, of Islamic origin or Islamic-like Orders. The aim of this text is to set a basis for this research and classification, to the extent permitted by its scope. This continuous phenomenon revives and settles, based on the conjuncture. It remains, however, dark and inaccessible, for the most part, because the Fraternities do not operate legally in all cases and are rather internalizing organizations which do not reveal their affairs to the “profane” society.